2001
DOI: 10.21273/hortsci.36.5.880
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Gas Exchange Response of 'Arapaho' Blackberry and Six Red Raspberry Cultivars to Moderate and High Temperatures

Abstract: Leaf gas exchange of six red raspberry (Rubus idaeus L.) and one blackberry (Rubus L. subgenus Rubus Watson) genotypes growing in 12-L containers was measured at four temperatures (20, 25, 30, and 35 °C) once a month for 3 months in growth chambers by infrared gas analysis. Measurements were taken on three successive leaves on the same primocane between the third and seventh nodes (≈75% to 85% of full leaf expansion). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 13 publications
3
12
1
2
Order By: Relevance
“…Although R. parviflorus and R. spectabilis do not have low physiological rates-the g s rates we measured were greater than many cultivated Rubus and other Pacific Northwest trees and shrubs in late spring (Waring and Franklin 1979;Stafne et al 2001)-both native Rubus species faced significant water limitation in summer. In effect, our results suggest that R. armeniacus experienced a less extreme summer drought even compared to these vigorous natives.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Although R. parviflorus and R. spectabilis do not have low physiological rates-the g s rates we measured were greater than many cultivated Rubus and other Pacific Northwest trees and shrubs in late spring (Waring and Franklin 1979;Stafne et al 2001)-both native Rubus species faced significant water limitation in summer. In effect, our results suggest that R. armeniacus experienced a less extreme summer drought even compared to these vigorous natives.…”
Section: Discussionmentioning
confidence: 56%
“…By maintaining high stomatal conductance, gas-exchange processes can be minimally curtailed under drought conditions such as those of Pacific Northwest summers (Stephenson 1990). Although stomatal conductance (g s ) is not always limiting to CO 2 assimilation (A) in Rubus species (Stafne et al 2001); McDowell and Turner (2002) found g s and A to be well correlated in both R. armeniacus and the Pacific Northwest native R. ursinus. A strong ability to maintain active gas exchange through both spring and summer conditions may make light more limiting than water to the invasive success of R. fruticosus.…”
Section: Implications For Invasionmentioning
confidence: 99%
“…; Stafne et al . ; Hall & Sobey ). We evaluated g m from 20 to 35 °C, which is representative of the maximal daytime T leaf differential experienced by raspberry leaves out in the open field on sunny summer days in southern Québec where plants were obtained.…”
Section: Introductionmentioning
confidence: 97%
“…In this study, we evaluated the short-term temperature response of g m in red raspberry (Rubus idaeus L.), an economically important horticultural crop of northern hemisphere origins, which readily adapts to cool temperate climatic conditions (Hall & Sobey 2013). Net photosynthesis in red raspberry is optimal below 25°C, peaking typically around 17-21°C (Percival et al 1996;Stafne et al 2001;Hall & Sobey 2013). We evaluated g m from 20 to 35°C, which is representative of the maximal daytime T leaf differential experienced by raspberry leaves out in the open field on sunny summer days in southern Québec where plants were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Einen negativen Einfluss der steigenden Temperatur (Bereich 10-30°C) auf die Pollenkeimung und damit letztendlich auf den zu erwartenden Fruchtansatz konnten Leech et al (2002) Stafne et al (2001) im Bereich von 20-35°C, mit einer 40%igen Abnahme, wenn die Temperatur von 20 auf 35°C anstieg. Nach Cameron et al (1993) liegt das Temperaturoptimum der Fotosynthese und damit der Kohlenhydratproduktion bei Himbeeren im Bereich von 12-20°C.…”
Section: Allgemeines Pflanzenwachstumunclassified